PENGARUH VARIASI FORMULASI TEH CELUP DAUN TEH HIJAU (Camellia sinensis) KOMBINASI SERAI (Cymbopogon nardus) DAN JAHE (Zingiber officinale) TERHADAP KADAR FLAVONOID - Haq, Athifa Afra Aulia; Endang Setyowati; Bintari Tri Sukoharjanti (Nusantara Hasana Journal, 2025)
Excess free radicals can trigger oxidative stress and contribute to degenerative diseases. Flavonoids, as natural antioxidants, neutralize free radicals and are therefore important in the development of functional beverages. This study aimed to evaluate sensory characteristics, panelist preference, and flavonoid content, and to determine the optimal formulation of tea bags containing green tea leaves (Camellia sinensis), lemongrass (Cymbopogon nardus), and ginger (Zingiber officinale). Four formulations were prepared: F1 (100% green tea), F2 (70:15:15), F3 (50:25:25), and F4 (30:35:35). Flavonoid content was determined by UV-Vis spectrophotometry, while sensory properties were assessed through organoleptic and hedonic tests. Panelists were aged 18–59 years, regular tea drinkers, with normal sensory ability, while exclusion criteria included pregnancy, breastfeeding, allergies, medication use. Results showed that F4 had the highest flavonoid content (49.397 ± 3.258 mg QE/L), followed by F3 (32.677 ± 3.703 mg QE/L), F2 (13.877 ± 1.960 mg QE/L), and F1 (11.117 ± 1.502 mg QE/L). Statistical analysis confirmed significant effects of formulation on flavonoid content and sensory attributes of color, aroma, and taste (p < 0.05). F4 was identified as the optimal formulation with superior flavonoid content and panelist acceptance.